Why the Bible began an alternative history of scripture and its origins - Wright, Jacob L. 1973- (New York Cambridge University Press, 2023)
Demonstrating how the Old Testament or Hebrew Bible represents the first, and one of the most elaborate, projects of 'peoplehood,' Wright tells the dramatic story of the Bible's origins in relation to 1) a longstanding political division between North and South (Israel and Judah) and 2) the traumatic experience of defeat.
Description based on publisher supplied metadata and other sources